(untitled) (Altre Modernità, 2017)
This article aims at analysing the spelling oddities in the still widely unknown corpus of the German-American poet Elsa von-Freytag Loringhoven (1874-1927). Such irregularities prove too widespread in her poetic work merely to be ascribed to her German origins, especially since her English was otherwise proficient, and since she had native speaker friends willing to proofread her writings. Although ‘the Baroness’ only learnt English in her thirties, recidivism in the misspelling of some particular words motivates further investigation. The Baroness’s poetic language is so rich in misspellings, mistranslations, coinages, portmanteau words and unusual idioms, that it is idiosyncratic and unique; clearly, a lack of proficiency in the English language cannot be identified as the (only) cause. Indeed, in a letter to Djuna Barnes, she declared: “It is written like half mad in syntax […] I am half mad – as is only sensible”. While such a statement is not to be taken literally, it is still true that the Baroness’s intolerance of social prescriptions, her alluring performances and daring behaviour caused her to be labelled as “hysteric, perverted and mad.” (Gammel 2003: 57) Spelling errors and other oddities in her corpus should therefore be reframed in a wider, programmatic intention to challenge the English language specifically, and verbal expression in general; ultimately, linguistic errors are one of the most interesting manifestations of her uncompromising non-acquiescence to rules.